THE EFFECT OF BIG BOOK AS MEDIA ON STUDENTS’ READING COMPREHENSION AT FIFTH GRADE OF ELEMENTARY SCHOOL - Mahayanti, N. W. S.; Artini, L.P.; Nur Jannah, I. A. (Universitas Pendidikan Ganesha, 2017)
This study was aimed at investigating whether or not there was a significant effect of the implementation of Big Book as media on reading comprehension achievement of the fifth grade students. This study was conducted in SD Laboratorium Undiksha Singaraja in the form of an experimental research with post-Test only Control Group Design. The population was the fifth grade in which two classes were selected as the sample of the study. Then, the samples were decided as the experimental group and control group by using lottery. The experimental group was taught by using Big Book as media and the control group was taught by using conventional media. The data were analyzed by using t-test through SPSS 17.0. The result of the data analysis showed that students in experimental group performed better than the students in the control group. It was proven by the result of the descriptive statistics that showed the mean score of the experimental group was 85.51 while the mean score of the control group was 75.56. The result of the t-test also showed that the value of Sig (2-tailed) 0.000 was less than 0.05. It can be concluded that there was a significant difference of reading comprehension achievement between students treated with big book as media and those treated using conventional media at fifth grade of elementary school in SD Laboratorium Undiksha Singaraja.